Effect of a 30-Month Health-Promoting Program on the Prevalence of Cardiovascular Risk Factors in Patients With First Episode Schizophrenia. (September 2020) - Søgaard, Hans J.; Højlund, Mikkel; Elliott, Anja; Viuff, Anne G.; Vandborg, Kirsten; Viuff, Jakob; Munk-Jørgensen, Povl; Hjorth, Peter
Abstract : Background: Lifestyle interventions aimed at reducing cardiovascular risk factors in patients with first-episode schizophrenia (FES) have shown modest efficacy, probably owing to a short observation period and the presumption of linear trajectories of cardiovascular risk factors. Study Question: How prevalent are abnormal cardiovascular values in patients with FES and how do cardiovascular risk factors develop during a 30-month program? Study Design: A 30-month naturalistic longitudinal study of 136 consecutively referred patients with FES from 2 outpatient clinics. The health-promoting program consisted of individual guidance, group sessions, and normal treatment and care. Measures and Outcomes: The prevalence of abnormal cardiovascular risk factors (body mass index, waist circumference (WC), body fat percentage, systolic and diastolic blood pressure, pulse, total cholesterol, high- and low-density lipoproteins, triglycerides, mean glucose, and visceral adiposity index) was estimated at index. The cardiovascular risk factor trajectories were analyzed with longitudinal mixed-effect models. Results: The patient with FES showed elevated cardiovascular risk factors at index. Thus, 56.8% of the patients were overweight in different grades and 50.4% had increased WC. A total of 81.8% had high level of body fat and hypertension prevalence with only 20% with normal blood pressure. Important changes during the intervention period were that the risk factors weight and WC were increasing the first 581 and 646 days, after which they decreased. Almost all cardiovascular risk factors worsened initially, improving after 1–2 years. Conclusions: Patients with FES show increases in cardiovascular risk factors at index. Short observation periods and the presumption of linear trajectories may indicate that the effect of health-promoting programs is ineffective, as the effects are curvilinear and improvements appear only after 1 year. The implication clinically is the importance of a long intervention period regarding lifestyle modifications to ascertain improvement among patients with FES.